(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Globally, the pandemic situation has compelled educational institutions to rally behind efforts to contain the spread of this virus. Throughout this lockdown, these occurrences prompted educational experts to consider unorthodox ways of instruction. Thus, it paved the path for digital learning. This research will assist with determining how students feel about digital classes and tests during the COVID-19 Pandemic. It was compiled using information received from students at various colleges/universities/institutions located throughout Tamil Nadu.